When states fail : causes and consequences - Rotberg, Robert I. (Princeton University Press, 2004)
Since 1990, more than 10 million people have been killed in the civil wars of failed states, and hundreds of millions more have been deprived of fundamental rights. The threat of terrorism has only heightened the problem posed by failed states. When States Fail is the first book to examine how and why states decay and what, if anything, can be done to prevent them from collapsing. It defines and categorizes strong, weak, failing, and collapsed nation-states according to political, social, and economic criteria. And it offers a comprehensive recipe for their reconstruction. The book comprises fo.